Does war moderate the association between mental wellbeing and its predictors among children? A multi-country cross-sectional study - Shanquan Chen; Sara Rotenberg; Hannah Kuper (BMC Psychiatry)
Abstract Background This study explores how war or conflict influences the established predictors of mental well-being among children, addressing a significant gap in current research. Methods Utilizing data from Multiple Indicator Cluster Surveys (MICS6) collected between 2016 and 2021, we examined children aged 5–17 years in four low or middle-low-income countries experiencing war or conflict and compared them to 20 control countries. We employed logistic models to analyze the data, focusing on mental well-being as the outcome. Primary independent variable was exposure to war, with an emphasis on the interaction between this exposure and potential predictors, including age, sex, having a physical disability, enrolled in education, having siblings, living with at least one parent, residence place, and family wealth status. Results The analysis revealed significant modifications in the association between factors like age, disability, education, economic status, and place of residence and mental well-being due to war (p values < 0.05). Specifically, the impact of war was more pronounced in older children (OR = 1.48, 95%CI = 1.18–1.85) compared to younger ones. Education was found to mitigate anxiety in conflict-affected areas (OR = 0.75, 95%CI = 0.60–0.95), whereas children with disabilities were more vulnerable to mental health challenges (OR = 2.05, 95%CI = 1.65–2.55) in these settings. Limitations The mental well-being measure was based on caregiver reports, which may not fully capture the children’s experiences. Conclusion Our findings provide crucial insights into the differential impact of war on children’s mental well-being. They underscore the need for tailored, context-specific mental health interventions for children in conflict-affected areas and encourage further research into the nuanced effects of war on child and adolescent mental health.